Animals in the study of public administration. (3rd August 2022) - Mitchell, Jerry
Abstract: The human‐animal experience has eluded the study of public administration. The evidence shows the field's top journals and textbooks have paid little attention to animals, public affairs degree programs are mostly without animal‐focused courses, and professional associations have failed to include, for the most part, animals as stakeholders whose interests should be considered. This lack of attention is out of step with a world confronting such wicked problems as animal cruelty, species extinction, and zoonosis. Practical ways are proposed for incorporating animal topics into scholarship, education, and the overall posture of the discipline. The expectation is that a focus on non‐human species can shapeshift the field toward a biocentric outlook and a truly authentic understanding of public affairs.